Diverse Effects, Complex Causes: Children Use Information About Machines' Functional Diversity to Infer Internal Complexity. Issue 3 (26th September 2016) - Ahl, Richard E.; Keil, Frank C.
Abstract : Four studies explored the abilities of 80 adults and 180 children (4–9 years), from predominantly middle‐class families in the Northeastern United States, to use information about machines' observable functional capacities to infer their internal, "hidden" mechanistic complexity. Children as young as 4 and 5 years old used machines' numbers of functions as indications of complexity and matched machines performing more functions with more complex "insides" (Study 1). However, only older children (6 and older) and adults used machines' functional diversity alone as an indication of complexity (Studies 2–4). The ability to use functional diversity as a complexity cue therefore emerges during the early school years, well before the use of diversity in most categorical induction tasks.